Construction of the pEGFP-N1-p53/MAR vector and its effect on HEP3B cell morphology - Li, Peng Shan; Lei, Xue Qin; Xu, Ting Sheng; Wang, Pan Lin; Song, Zhen; Li, Zhen Hong; Han, Xue Mei (Penerbit Universiti Kebangsaan Malaysia, 2018)
Cancer always presents a big problem that endangers human health. In recent years, the use of gene therapy in cancer research has significantly increased. This study aimed to construct a non-viral, wild-type, recombinant eukaryotic expression vector, pEGFP-N1-p53/MAR and verify its mechanism of action in cancer cells in vitro. This investigation provides a novel strategy for p53 gene therapy via regulation of the matrix attachment region (MAR), potentially laying a foundation for the establishment of an anticancer protein bioreactor. The p53 gene was cloned from human peripheral blood and the MAR gene was amplified from chicken liver tissue. The recombinant eukaryotic expression vector pEGFP-N1-p53/MAR was constructed using an E. coli self-replication system. LipofectamineTM 2000 was used as the transfection agent to deliver the plasmid into the human hepatic carcinoma (HEP3B) cell line. We divided the groups as follows: negative control cells without plasmid transfection, vehicle control cells transfected with the PEGFP-N1 vector, and experimental cells transfected with the pEGFP-N1-p53/MAR vector. Cells in each well of the vehicle control and experimental groups were transfected with 1.6 μg of plasmid and 3 μL of liposome. The cellular morphology of each group was analysed using green fluorescence microscopy at 12, 24, 36 and 48 h. Then, statistical analysis of the apoptosis rates among the three groups was performed using SPSS. The ultrastructures of the cells were observed via transmission electron microscopy after transfection for 24 h. Morphological analysis showed that the cells of the experimental group were shrunken and reduced in size and their intercellular connections had disappeared. Additionally, the apoptosis rate in the experimental group was significantly higher than that in the control groups and the cellular microstructure showed that heterochromatin and apoptotic bodies were found in the experimental group. In conclusion, compared with the control groups, the pEGFP-N1-p53/MAR plasmid can effectively promote Hep3B cell apoptosis in vitro.